PENGARUH PENGENDALIAN INTERNAL, AUDIT INTERNAL, MORALITAS INDIVIDU DAN BUDAYA ORGANISASI TERHADAP PENCEGAHAN KECURANGAN (Studi Empiris pada Inspektorat Kabupaten Kampar) - Annisa Fitri; Nanda, Nanda Suryadi (Jurnal Akuntansi Kompetif, 2024)
The purpose of this study is to test the hypothesis and produce evidence regarding the Influence of Internal Control, Internal Audit, Individual Morality and Organizational Culture on Fraud Prevention (Empirical Study at the Inspectorate of Kampar Regency). This study uses Primary data, namely distributing questionnaires to Respondents at the Inspectorate who know the relationship between Internal Control, Internal Audit, Individual Morality and Organizational Culture on Fraud Prevention. The sampling used in this study is the Total Sampling method. The number of Respondents who were sampled in this study was 44 Respondents. The analysis method used to test the hypothesis is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the SmartPLS 4.0 analysis tool.The results of this research show that Internal Audit has a positive and significant effect on Fraud Prevention, but Internal Control, Individual Morality and Organizational Culture do not have a positive and insignificant effect on Fraud Prevention at the Kampar Regency Inspectorate.